151P Investigation of the mechanism of action of anti-PD-1 treatment by systematic depletion of different immune cell populations in syngeneic models. (15th December 2019) - Bourre, L; Jin, Y; Muntel, J; Yu, H; Beeler, K; Bruderer, R; Shan, Y; An, A Xiaoyu; Ouyang, D Xuesong; Li, H Qixiang
Abstract: Background: Human cancers are heterogenic and thus response to immune checkpoint inhibitors (ICIs) such as anti-PD-1 or anti-PD-L1 antibody treatments can be vastly different, with only ∼20% of treated patients responding and some initial responders developing resistance. However, the mechanism of action (MOA) underlying these differences has yet to be revealed. In this study we treated syngeneic tumor-bearing mice with anti-PD-1 antibody in combination with targeted immune cell depletion in order to understand how different lineages of immune cells impacted anti-PD-1 efficacy. Methods: Selected immune cell subpopulations were depleted in four different subcutaneous murine syngeneic models (MC38, CT26.WT, EMT6 and Hepa 1-6) and anti-PD-1 (10mg/kg) was administered either following the depletion (only for anti-CD25) or concurrently with the depletion antibodies. The effectiveness of each depletion was assessed by flow cytometry analysis of tumor, blood and spleen at the end of each study. Tumor samples from few sub-groups of MC38 and Hepa1-6 models were processed for proteomics analysis (collaboration with Biognosys). Results: As expected, depletion of CD8+ T cells completely abolished the antitumor effects of anti-PD-1 treatment in MC38, EMT6 and CT26.WT, confirming the crucial roles of CD8+ T cells in tumor killing; Interestingly, anti-PD-1 efficacy in Hepa1-6 was only modestly attenuated by eliminating CD8+ T cells, indicating a vital role of non-CD8+ effector cells in mediating anti-PD-1 efficacy in this particular line. Depletion of NK showed a minor impact on the efficacy of anti-PD-1 treatment, whereas the depletion of macrophages largely promoted the efficacy of anti-PD-1 in MC38 and CT26.WT; however, weakening the effect of anti-PD-1 in the Hepa 1-6 model. Depletion of Treg demonstrated synergistic effects with anti-PD-1 treatment in controlling CT26.WT and EMT6 tumors. Conclusion: Our studies show an unequivocal role of CD8+ T cells in anti-PD-1 induced tumor growth inhibition. However, other immune cell lineages may act differently upon PD-1 blockade release, presumably depending on specific tumor microenvironment. Legal entity responsible for the study: The authors. Funding: CrownBio, Biognosys. Disclosure: All authors have declared no conflicts of interest.